Concise Review: Custodians of the Transcriptome: How MicroRNAs Guard Stemness in Squamous Epithelia. (24th March 2015) - Ning, Matthew S.; Andl, Thomas
Abstract: At the core of every dynamic epithelium resides a population of carefully regulated stem cells ensuring its maintenance and balance. The complex mammalian epidermis is no exception to this rule. The last decade has delivered a wealth of knowledge regarding the biology of adult stem cells, but questions still remain regarding the intricate details of their function and maintenance. To help address these gaps, we turn to the small, single-stranded RNA molecules known as microRNAs. Since their discovery, microRNAs have provided us with novel insights and ground-breaking impulses to enhance our understanding of the biological sciences. Due to their unique role in post-transcriptional regulation, microRNAs are essential to cutaneous biology as well as the epidermal stem cell. By serving as buffers to balance between epithelial stemness, proliferation, and differentiation, microRNAs play essential roles in the maintenance of cutaneous stem cells and their transition out of the stem cell compartment. Following an updated overview of microRNA biology, we summarize the current knowledge of the role of microRNAs in cutaneous stem cells, focusing on three major players that have dominated the recent literature: miR-205, miR-203, and miR-125b. We then review clinical applications, discussing the potential of microRNAs as therapeutic targets in regenerative and oncological stem cell-based medicine. Stem Cells 2015;33:1047–1054